"A Tale of Two Planes": Deep Versus Superficial Serratus Plane Block for Postmastectomy Pain Syndrome. Issue 2 (1st March 2017) - Piracha, Mohammad M.; Thorp, Stephen L.; Puttanniah, Vinay; Gulati, Amitabh
Abstract : Introduction: Postmastectomy pain syndrome (PMPS) is a significant burden for breast cancer survivors. Although multiple therapies have been described, an evolving field of serratus anterior plane blocks has been described in this population. We describe the addition of the deep serratus anterior plane block (DSPB) for PMPS. Methods: Four patients with history of PMPS underwent DSPB for anterior chest wall pain. A retrospective review of these patients' outcomes was obtained through postprocedure interviews. Results: Three of the patients previously had a superficial serratus anterior plane block, which was not as efficacious as the DSPB. The fourth patient had a superficial serratus anterior plane that was difficult to separate with hydrodissection but had improved pain control with a DSPB. Conclusions: We illustrate 4 patients who have benefitted from a DSPB and describe indications that this block may be more efficacious than a superficial serratus plane block. Further study is recommended to understand the intercostal nerve branches within the lateral and anterior muscular chest wall planes.